The Decline of Commodity Prices and Global Agricultural Trade Negotiations: A Game Changer? - Christophe Bellmann; Jonathan Hepburn (Revue Internationale de Politique de Développement)
With food prices reaching their lowest levels since 2006, governments have been under increased pressure to increase tariff protection or provide state aid to guarantee remunerative prices and maintain farm income domestically, often at the expense of smaller countries that cannot compete with the treasuries of large agriculture players. A review of trade-restrictive measures applied in the last 10 years confirms the resurgence of such isolating trade policies and a significant shift towards more government subsidies and market access protection. Based on this data and a review of recent policy changes in major economies such as the EU, US and China, this paper assesses the possible implications of this new price environment for future reforms of agricultural policies, including the prospects for removing trade distortions as envisaged under the 2030 Development Agenda.